2019
DOI: 10.22515/jifa.v2i1.1590
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Tata Kelola Terhadap Akuntabilitas Pengelolaan Dana Desa Dengan Profesionalisme Sdm Dan Integritas Sebagai Variabel Intervening

Abstract: ARTICLES INFORMATION AbstractThe aim of this study is to analyze the effect of financial governance to the village fund allocation accountability with professionalism and integrity as intervening variable. The sample of this study is the village secretary in Magetan Region. The number of samples according to the criteria were processed in this study was 122 respondents. The analysis method using Structural Equation Modelling with Partial Least Square. The results showed that financial governance of village had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…The type of data in this study is primary data which were obtained directly from the primary data sources, The data were collected using questionnaires distributed to the village government circle in Magetan Regency. This research selected Magetan Regency because of the contradiction captured between the previous study results (Agustiningrum et al, 2020;Juliana & Widhianningrum, 2017;Kirowati et al, 2017;Ubaidillah, 2019;Zulaikah et al, 2018) and the facts of fraud cases in this regency (Kompas.com, 2020). Convenience sampling method was used for data gathering.…”
Section: Samplementioning
confidence: 93%
See 1 more Smart Citation
“…The type of data in this study is primary data which were obtained directly from the primary data sources, The data were collected using questionnaires distributed to the village government circle in Magetan Regency. This research selected Magetan Regency because of the contradiction captured between the previous study results (Agustiningrum et al, 2020;Juliana & Widhianningrum, 2017;Kirowati et al, 2017;Ubaidillah, 2019;Zulaikah et al, 2018) and the facts of fraud cases in this regency (Kompas.com, 2020). Convenience sampling method was used for data gathering.…”
Section: Samplementioning
confidence: 93%
“…Several studies on the implementation of village fund management in Magetan Regency showed that the village government officials attempted to exercise integrity, accountability and transparency in managing the village fund to improve the village economy (Agustiningrum et al, 2020;Juliana & Widhianningrum, 2017;Kirowati et al, 2017;Ubaidillah, 2019;Zulaikah et al, 2018). The studies also showed that the accountability on the programs related to village fund management was quite good, but still less efficient in the financial accountability.…”
Section: Introductionmentioning
confidence: 99%
“…Kemudian pada penelitian terdahulu yang berikutnya ditulis oleh (Ubaidillah & Arumsari, 2019) Dari permasalahan yang terjadi diatas, maka peneliti tertarik untuk meneliti penelitian dengan judul "Integritas Perangkat Desa Dalam Pengelolaan Dana Desa (studi kasus : Kantor Desa Minta Kasih Kecamatan Salapian Kabupaten Langkat).…”
Section: Pendahuluanunclassified
“…The village chief has the duty to manage the village economy in the form of money or commodity related to the village rights and obligations measurable in money, and the fulfillment of the village rights and obligations, resulting in expenses, income, and financing (Aprilia, 2019;Sofyani & Tahar, 2021). The village fund budget is used for apparatus spending costs of 30% and costs for village government operations in empowering village communities by 70% (Ubaidillah, 2019;Zulkifl et al, 2021).…”
Section: Introductionmentioning
confidence: 99%